THE CONCEPT OF GLOBAL CITIZENSHIP- PHILOSOPHICAL AND SOCIOPOLITICAL INTERPRETATION (SCIENCE TIME JOURNAL, 2026)
Global citizenship has become one of the most significant concepts in contemporary political philosophy and social sciences. In the context of globalization, increasing interdependence among nations, rapid technological development, and global challenges such as climate change, migration, poverty, and human rights issues, the idea of global citizenship has gained theoretical andpractical relevance. This article examines the philosophical foundations and socio-political interpretations of global citizenship. The study analyzes the evolution of the concept from classical cosmopolitanism to modern global governance theories and explores its role in promoting social responsibility, intercultural dialogue, democratic participation, and global solidarity. The article concludes that global citizenship represents not only a legal or political identity but also an ethical and cultural framework for addressing global problems collectively.